Bamboo as Geogrid Material for Improvement in Road Construction - Marzuki, Najma Amira; Zainorabidin, Adnan (Recent Trends in Civil Engineering and Built Environment, 2023)
Bamboo or its scientifically known as Bambusoideae is now extensively used for construction materials since they have good bending strength, durability and the speed of growth contribute to making bamboo a very popular and sustainable material for building and road construction. The aim of this study is to evaluate the performance of bamboo as geogrid material for improvement in road construction as to overcome poor soil conditions that lead to unsatisfactory performance of road pavements. The objective of this study is to study the mechanical properties of untreated bamboo by compressive strength test, to determine the shear parameter of soil sublayer with and without bamboo geogrid reinforcement using physical laboratory model and to analyse the performance layer of bamboo geogrid in the soil sublayer. Type of bamboo used for this study is Gigantochloa Scortechinii or locally known as buluh semantan/buluh galah undergone compressive strength test. The vane shear test is to determine the shear parameter of soil sublayer. Then, the performance of bamboo geogrid in the soil sublayer has been analyzed by monitoring the settlement that occur by applying a constant load of 2 kPa for controlled model, one layer of bamboo geogrid and two layers of bamboo geogrid. The results obtained shown an improvement for settlement occurred using two layers of bamboo geogrid as reinforcement for the peat soil sample.